A TDR Array Probe for Monitoring Near‐Surface Soil Moisture Distribution. Issue 4 (13th April 2017) - Sheng, Wenyi; Zhou, Rong; Sadeghi, Morteza; Babaeian, Ebrahim; Robinson, David A.; Tuller, Markus; Jones, Scott B.
Abstract : Core Ideas: A TDR array has been developed for soil moisture profiling. The sensor provides eight incremental measurements at centimeter‐depth resolution. Permittivity, evaporation rate, and soil moisture profile were determined. Near‐surface soil conditions (i.e., moisture and temperature) moderate mass and energy exchange at the soil–atmosphere interface. While remote sensing offers an effective means for mapping near‐surface moisture content across large areas, in situ measurements, targeting those specific remotely sensed soil depths, are poorly understood and high‐resolution near‐surface measurement capabilities are lacking. Time domain reflectometry (TDR) is a well‐established, accurate measurement method for soil dielectric permittivity and moisture content. A TDR array was designed to provide centimeter‐resolution measurements of near‐surface soil moisture. The array consists of nine stainless steel TDR rods spaced 1 cm apart, acting as waveguide pairs to form eight two‐rod TDR probes in series. A critical aspect of the design was matching the spacing of the coaxial cable–TDR rod transition to avoid unwanted reflections in the waveforms. The accuracy of the TDR array permittivity measurement (±1 permittivity unit) was similar to that of conventional TDR as verified in dielectric liquids. Electric field numerical simulations showed minimal influence of adjacent rods during a given rod‐pair measurement. The evaporation rate determined by the TDR array compared well with mass balance data in a laboratory test. Near‐surface soil moisture profile dynamics were monitored at centimeter‐depth resolution using the TDR array in a field experiment where volumetric moisture content estimates (0–8 cm) were within 2% of conventional three‐rod TDR probes averaging across 0 to 8 cm and from 1‐ to 3‐cm depths.